Policy analysis matrix for livestock industry in Peninsular Malaysia - Adha, Zulheri (2011)
The main objective of this study was to assess the comparative advantage of livestock sectors in Peninsular Malaysia. The study analyzed livestock productions, namely broiler, layer, beef cattle, and goat in Negeri Sembilan, Perak and Selangor. This study used a Policy Analysis Matrix (PAM) to determine whether livestock productions have comparative advantage if produced under large, medium or small production scale. The primary data were collected through an in-depth interview with farmers using structured questionnaire. Data were collected from 39 broiler farmers, 18 layers farmers, 39 beef farmers, and 40 goat farmers in Peninsular Malaysia. The results of the study indicated that the non-ruminant sector which consists of broiler and layer sub-sector showed positive results on the ratio of social profitability for all types of farm scale. These results mean that the broiler and layer farm were profitable if managed in either small, medium, or large scale. The ruminant sector on the other hand showed that, the beef farm would only generate profit if managed in a large scale. While goat production is capable of generating profits if managed in large and medium scale of operation. Domestic Resource Cost (DRC) ratio as the comparative advantage indicator shows that broiler farm in large scale has DRC ratio of 0.24 and layer farm in medium scale has DRC ratio of 0.26. In the ruminant sector, goat were produced in large scale has DRC ratio of 0.43 while beef produced in large scale with DRC ratio of 0.81. All of farms have a comparative advantage when their ratio implies that the value added per unit of products is larger than the value of domestic resources used to produce that unit. As a result, broiler farm in large scale with DRC ratio of 0.24 has a greatest comparative advantage in the Malaysian livestock industry. Based on the level of comparative advantage, this study recommends that the Malaysian livestock industry should focus on poultry to manage the broiler farm. Moreover, the government was asked to provide support for production, distribution and trade of broiler can take place with more profitable.